(untitled) (Asian Journal of Medical and Biological Research, 2020)
Increasing demand, uncertain availability, and increasing cost for fishmeal (FM), fish nutritionists have been driven to find alternative sources of protein. The aim of this study was to evaluate the effects of substituting FM with soybean meal (SM) on growth performance of silver barb, Barbonymus gonionotus. Five diets were prepared 0%SM (100%FM), 25%SM (75%FM), 50%SM (50%FM), 75%SM (25%FM) and 100%SM (0%FM) by replacing FM with SM. B. gonionotus having initial length and weight of 8.62±0.9 cm and 8.80±3.11 gm were fed each diet twice a day for 45 days. Fish sampling was done fortnightly. Significantly higher (P<0.01 and P<0.05) weight and length gain were found up to 75%SM compared to 100%SM. The specific growth rate (6.01±0.34%d-1) was significantly higher (P<0.05) in 50%SM compare to 75%SM and 100%SM. Considering the result of present study we recommend to replace 50% SM as a source of protein with 50% FM for better growth of B. gonionotus. Asian J. Med. Biol. Res. June 2020, 6(2): 149-154